Machine Learning and Brain Imaging: Opportunities and Challenges. Issue 10 (October 2019) - Paulus, Martin P.; Kuplicki, Rayus; Yeh, Hung-Wen
Abstract : Machine learning approaches may provide ways to link brain activation patterns to behavior at an individual-subject level. Using a comparative performance analysis, Jollans and colleagues ( Neuroimage, 2019) highlight in a recent paper key considerations when applying machine learning algorithms to neuroimaging data.